Experimental investigation of effect of stratified charging system adopted to gasoline engine running with LPG on engine performance - Can, I.; Oner, C.; Sugozu, I. (Elsevier Sci Ltd, 2013)
The energy conversation and values of limited emission level are very important issue for manufacturers and engine designers. Therefore the investigations about homogeneous charge engine and stratified charge (SC) engine have commonly been considered by the literatures. Homogeneous charge engines run with stoichiometric mixture, and SC engines run with lean mixture. The main purpose of this study, in order to run with poor mixture of gasoline engine like diesel engine, the shape of charge was converted to SC and used liquid petroleum gases (LPG) fuel. In this point of view, LPG-air mixture is prepared in two different environments and rates, and the mixture was taken into the engine as stratified by two steps. The effects of engine performance, fuel consumption and emission characteristics are investigated for SC application. The experiments were made under full load and full throttle position. According to the results of the experiments, both the engine power and torque did not change and the fuel consumption was achieved in reduction by 15%. In addition, improvements have been obtained in value of emission.
Keywords: Stratified charge; Engine performance; Fuel consumption; Emission characteristics; LPG